2000
DOI: 10.1180/002646100549544
|View full text |Cite
|
Sign up to set email alerts
|

Primary zoning in pyrochlore group minerals from carbonatites

Abstract: Pyrochlore group minerals have the general formula A16–xB16O48Z8–y·nH2O, with A mainly Na, Ca, Sr, REE, Th, U; B mainly Nb, Ta, Ti and Z being O, F, OH. In this study, pyrochlore specimens were examined from carbonatites at Argor, Carillon Dam, Chilwa Island, Fen, Lueshe, Oka, Mbeya, Meech Lake and Verity. Primary features include a background with little compositional variation, from core to rim, upon which are commonly superimposed narrow oscillatory zones, parallel to {111}. These zones are usually characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 24 publications
4
49
0
1
Order By: Relevance
“…They discussed possible mechanisms to compensate for the charge defi ciency caused by the presence of Si (up to 0.70 apfu) on the B site. Contrary to this view, Hogarth et al (2000) suggested that the presence of Si (ranging from 3.03 to 3.84 wt% SiO 2 ) in the metamict, zoned uranpyrochlore from McCloskey's Field (Quebec) was due to impurities of sub-micrometer silicate phases rather than to a Si ↔ Nb substitution.…”
Section: Occurrence Of "Silicified" Pyrochloresmentioning
confidence: 78%
“…They discussed possible mechanisms to compensate for the charge defi ciency caused by the presence of Si (up to 0.70 apfu) on the B site. Contrary to this view, Hogarth et al (2000) suggested that the presence of Si (ranging from 3.03 to 3.84 wt% SiO 2 ) in the metamict, zoned uranpyrochlore from McCloskey's Field (Quebec) was due to impurities of sub-micrometer silicate phases rather than to a Si ↔ Nb substitution.…”
Section: Occurrence Of "Silicified" Pyrochloresmentioning
confidence: 78%
“…The pyrochlore structure (Fd3 ̅ m) with the ideal formula Y is an anion-deficient derivative of the fluorite structure (AX 2 ) type with ordered cation sites [8][9][10][11]. Pyrochlore consists of corner-sharing BX 6 octahedra and A 2 Y chains with eight-fold-coordinated A cations [11][12][13][14] (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…However, major Ta enrichment is rare in carbonatites (Bagdasarov, 2009). Oscillatory zoning in the primary pyrochlore may reflect supersaturation in Nb, Ti and Th in the carbonatite melt (Hogarth et al, 2000). On the other hand, changes in the proportions of HFSE in the A and B sites, coupled with changes in the F content may be important (see Bambi et al, 2012).…”
Section: Discussionmentioning
confidence: 99%